Does Juan Carlos or Nelson Obtain a Larger Price Cut in the Spanish Housing Market? - Catia Nicodemo; Josep M. Raya (Institute of Labor Economics (IZA), 2018)
Using a unique dataset a non-parametric decomposition, we determined whether immigrants with native name, immigrants with foreign name and natives have different outcomes in Spain's housing market. Results suggest there are significant price discounts for immigrants with native names relative to immigrants with non-Spanish names. As a robustness check we prove that this is not due to the country of birth. We observe that most of the difference in price across immigrant groups remains unexplained, which may imply some form of discrimination (pure or statistical) against immigrants with non-native names.
Keywords: R1; R3; J7; 330; house price; price cut; discrimination; housing; matching method